(untitled) (BIRDEM Medical Journal, 2022)
Background: There is an association between intrauterine growth retardation (IUGR) and subsequent development of diabetes mellitus, coronary artery disease and hypertension during adult life. With this context, it is vital to give attention about the patterns of body proportion of IUGR babies. The aim of this study was to determine the proportion of asymmetric distribution IUGR in contrast to symmetric distribution among babies with low birth weight (LBW). Methods: This cross-sectional study was conducted in the Department of Pediatrics, Sher-e-Bangla Medical College, Barisal,from January 2012 to June 2012, with a total 114 babies with LBW. All singleton newborns, within 24 hours of birth, having birth weight < 2.5 kg was were included. Weight was plotted in weight for gestation age centile chart. Then Ponderal index (PI) was calculated to determine asymmetric and symmetric IUGR by using the formula. Convenient sampling was used. Data were analyzed with SPSS. P value <0.05 was considered as significant. Results: Out of 114 LBW babies, 79 were IUGR babies. Among 79 IUGR babies, 45.6% were male and 54.4% were female. The mean age of the mothers of the IUGR babies was 24.2 ± 5.6 years. Most of the mothers were in the age group of 16 to 25 years. In this study, most of the IUGR was asymmetric (68.4%) and a majority of the asymmetric IUGR babies were from rural areas. The PI of the asymmetric IUGR was significantly (p =<0.001) lower than the symmetric IUGR. Conclusion: This study highlights that, among the LBW babies most of them were IUGR, the large population of IUGR babies were of asymmetric patterns. This group of patients carries immense importance to keep an eye on the risk of fetal origin of adult diseases. BIRDEM Med J 2022; 12(3): 177-181